Experimental comparison of thermal conditions in office rooms: Diffuse ceiling ventilation, chilled beam system, and chilled ceiling combined with mixing ventilation. (27th May 2020) - Lestinen, Sami; Mustakallio, Panu; Kilpeläinen, Simo; Kosonen, Risto; Jokisalo, Juha; Koskela, Hannu; Melikov, Arsen Krikor
Abstract : Thermal environments generated by diffuse ceiling ventilation (DCV), chilled beam (CB), and chilled ceiling with mixing ventilation (CCMV) systems were compared at different heat loads. Experiments were carried out in two test chambers, in which a double office layout was investigated near heated windows. The heat load strength was increased from a normal level of 37–40 W/floor-m 2 to a peak load level of 57–64 W/floor-m 2 to observe effects on indoor air thermal conditions and draft discomfort. The target indoor air temperature was 26 ± 0.5 °C in the occupied zone. The results show that the air temperature, air speed, and draft rate levels were reasonable at a normal load and increased slightly at peak load conditions. The CCMV system provided the smallest share of locations in which the draft rate level was higher than 10%. None of the studied systems achieved the category A defined by EN ISO 7730. However, all the systems fulfilled the demands of category B, except for CB, which fell to category C at the peak load conditions by exceeding the draft rate limit in one location. Thermal conditions were at a similar level for the studied systems. However, CCMV may reduce slightly the draft discomfort.